THE IMPACT OF CRYPTO-ASSET UTILIZATION AS PAYMENT INSTRUMENT TOWARD RUPIAH AS LEGAL TENDER IN INDONESIA - Ruru, Bacelius; Tjager, I Nyoman; Mayasari, Amalia; Adhistita, Agradinda; Santro, August; Hasta Anggara, Muhammad Raffi (Journal of Central Banking Law and Institutions, 2022)
The utilization of Cryptocurrency increased across the globe. This phenomenon has led to varied responses from countries concerning whether this new phenomenon will affect the national monetary policy. As one of the countries where Cryptocurrency usage has flourished, Indonesia has reacted to its utilization. To this day, Indonesia has clearly stated that CryptoAsset (referring to Cryptocurrency) is considered as a tradable commodity, but not as a payment instrument. However, this policy does have not decreased the utilization of Cryptocurrency in Indonesia, proven by its market capitalization which has kept increasing over the years. This article thoroughly discusses Cryptocurrency utilization as a payment instrument, and how it will affect the legal tender (The Rupiah) in Indonesia. This article also analyzes the extent to which Cryptocurrency will affect the payment systems in Indonesia and how Bank of Indonesia will counter the Cryptocurrency’s utilization as a payment instrument within Indonesia’s jurisdiction.